Prince Caspian : the return to Narnia - Lewis, C. S. (Clive Staples), 1898-1963.; Baynes, Pauline (New York : HarperCollins, 2007)
Four children help Prince Caspian and his army of Talking Beasts to free Narnia from evil.
5.6.
5.6
5-8
Keywords: Good and evil -- Juvenile fiction; Narnia (Imaginary place) -- Juvenile fiction; Princes -- Juvenile fiction; Fantasy; Good and evil -- Fiction; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Good and evil -- Fiction; Narnia (Imaginary place) -- Fiction; Princes -- Fiction; Fantastic fiction; Fantastic fiction